2013
DOI: 10.5897/ajps2013.1053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra-row spacing on yield and quality of some onion varieties (Allium cepa L.) at Aksum, Northern Ethiopia

Abstract: Lack of improved varieties and production practices have been the major bottlenecks of onion production and productivity in Tigray, particularly at Aksum area. There have been no recommended intra-row spacing and variety for that area specifically; rather farmers used to practice non-uniform plant spacing. Thus, a field experiment was conducted to investigate the influence of intra-row spacing, variety and their interactions on yield, shelf life and bulb quality of onion, thereby recommend the optimum practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 13 publications
13
17
0
Order By: Relevance
“…Dz-sht-157-1B and Dz-sht-91-2B varieties produced the longest plants than Yheras Table 1. In line with the present findings, Yemane, et al [11] found significant genotypic variation in plant height. Furthermore, Tegbew [25] indicated the mean plant height of Adama Red (62.25 cm) cultivar was significantly higher than Bombay Red (56.04 cm).…”
Section: Plant Heightsupporting
confidence: 93%
See 3 more Smart Citations
“…Dz-sht-157-1B and Dz-sht-91-2B varieties produced the longest plants than Yheras Table 1. In line with the present findings, Yemane, et al [11] found significant genotypic variation in plant height. Furthermore, Tegbew [25] indicated the mean plant height of Adama Red (62.25 cm) cultivar was significantly higher than Bombay Red (56.04 cm).…”
Section: Plant Heightsupporting
confidence: 93%
“…In agreement with this result, Fikadu [23] obtained the longest plant height (27.28 cm) of shallot at intra-row spacing of 15 cm followed by 24.65 cm with the spacing of 20 cm; while the shortest plants (22.66 cm) at 10 cm intra-row spacing. Moreover, results are also in agreement with the findings of Yemane, et al [11] and Sara, et al…”
Section: Plant Heightsupporting
confidence: 92%
See 2 more Smart Citations
“…Yield is a very complex trait that can be impacted by genetic base and agro/ecological adaptation (PAVLOVIĆ et al, 2002), composition of growth media (SUTHAMATHY and SERAN, 2011), planting date (HAMMA, 2013), degree of plant population (KAHSAY et al, 2013), fertilization (BRDAR JOKANOVIC et al, 2011) etc. Yield is a very complex trait due to gene action and interaction with the environment, i.e., different reactions of genotypes on changeable environmental conditions (MARJANOVIĆ JEROMELA et al, (2011).…”
Section: Introductionmentioning
confidence: 99%